The implementation of project oriented problem based learning in a psychology course - Alwi, Azlin; Hussin, Ruhaya (2018)
Project-oriented problem based learning (POPBL) is an alternative approach to innovative teaching and is widely implemented in the classroom. However, little information is gathered pertaining to its implementation in psychology-related subjects. The present study is guided by two objectives: 1) to discuss the implementation of POPBL in a psychology course; and 2) to determine students’ perception of this type of approach to learning in the classroom. In the context of this study, POPBL was implemented in one of the psychology core courses, which is the Psychology of Human Relations. The results from the present study suggested that the POPBL was indeed highly acceptable and favored by all students. These findings were further discussed with respect to the current literature on teaching and learning approaches.